IN-SITU APPLICATION OF ELECTROMAGNETIC WAVES IN COMBINATION WITH BOTANICAL EXTRACTS TO ENHANCE THEIR EFFECTIVENESS IN CONTROLLING SUCKING INSECT PESTS OF COTTON - Muhammad Asif Farooq; Muhammad Furqan Ali; FARRUKH baig; Asim Abbasi; Bilal Atta (Journal of Animal and Plant Sciences, 2026)
Sucking insect pests pose serious threats to various crops, necessitating effective integrated pest management (IPM) strategies. This study explores residue-free, alternative pest control techniques usingelectromagnetic waves in synergy with botanical extracts of Azadirachta indica (Neem), Moringa oleifera (Moringa), and Citrus limon (Lemon) for managing key sucking pests: Bemisia tabaci, Aphis gossypii, Amrasca biguttula, Oxycarenus hyalinipennis, and Thrips tabaci. Laboratory experiments were conducted under a Completely Randomized Design (CRD) with five microwave exposure durations (0, 5, 10, 15, and 20 seconds) and four concentrations (5%, 10%, 15%, and 20%) of each botanical extract, each replicated three times. Microwaves at 2.4 GHz were applied using a custom-built device. The 20-second exposure time resulted in the highest mortality across all insect species, with B. tabaci (27.6%), A. gossypii (22.3%), A. biguttula (21.1%), O. hyalinipennis (22.5%), and T. tabaci (21.8%). When combined with botanical extracts, mortality significantly increased—maximum mortality occurred after 72 hours with 20% A. indica (24.38%), M. oleifera (24.44%), and C. limon (21.54%) extracts. Integrating microwaves with botanicals demonstrated significant synergistic insecticidal activity under controlled laboratory conditions. This innovative, residue-free approach offers a viable alternative to synthetic insecticides, aligning with sustainable pest management goals. Future research should focus on field-scale validation, optimization of microwave delivery systems, and phytochemical profiling of botanicals to enhance efficacy and scalability.
Keywords: Microwaves; Plant extracts; Cotton; Sucking pest complex; Mortality